Asuhan Keperawatan Pada Tn.N Dengan Gangguan Konsep Diri: Harga Diri Rendah - Moni Kuntari; Sri Nyumirah (AKPER Pasar Rebo, 2019)
Low self-esteem is a feeling of worthlessness, insignificance and prolonged inferiority due to negative evaluations of oneself and self-ability. The loss of self-confidence, feeling like a failure because it is unable to achieve desires according to self-ideals. Someone who experiences low self-esteem will tend to be shy and aloof when in a public place, and prefers to withdraw from social life. Based on the impact of low self-esteem above the role of nurses is needed in carrying out nursing care, namely promotive, preventive, curative and rehabilitative. Nursing care is done by interviews, both to clients, nurses and families, nursing actions are carried out directly on the client with the assistance of nurses. The client experiences low self-esteem because the client is attacked by residents in the home environment of his ex-lover because client often come to the home of his ex-lover. Nursing diagnoses that can be found in clients are low self-esteem, social isolation, risk of sensory perception disorders: hallucinations and self-care deficits. Nursing planning is carried out in accordance with Hospital standards. Nursing evaluation can be seen in the client being able to identify the positive abilities possessed by the client, carrying out the abilities possessed, namely singing, sweeping, folding clothes and tidying up the bed. Another ability achieved by the client is able to get to know one person or more, controlling the hallucinations that arise and the client can maintain his cleanliness.